Stress failure of cement concretes under compression – synthesis of knowledge, conclusions - Gorzelanczyk, Tomasz; Hoła, Jerzy (Journal of Civil Engineering and Management, 2014)
This paper presents a synthetic review of the existing knowledge on the stress failure of cement concretes under compression, based on the available literature and the authors’ own research. It is pointed out that there is no knowledge on the stress failure of new-generation concretes, which needs to be acquired through proper research. The usefulness of the knowledge on the stress failure of concrete under compression for building practice is highlighted.First published online: 04 Jul 2014